EVALUASI DAN PROGRAM PEMELIHARAAN JEMBATAN DENGAN METODE BRIDGE MANAGEMENT SYSTEM (BMS) (Studi Kasus : Empat Jembatan Propinsi D.I. Yogyakarta) - Hariman, Ferry; Christady H., Hary; Triwiyono, Andreas (Civil Engineering Forum Teknik Sipil, 2007)
Bridge is among the important part in transportation system. If the bridge damage or collapse it will definitely affect the transportation and distribution of human and goods. Thus it is very important to maintain bridge appropriately. Accordingly Bridge Management System (BMS) is a standard mechanism to evaluate condition and function of the bridge. The BMS also can be used to decide necessary treatment to maintain the bridge in specific circumstances. Further more Computer-Based BMS combined with integrated information system can shows us the priority scale to manage the bridge maintenance. But the visual assessment of bridge is a necessary step to evaluate general conditions of the bridge. This research conducted in four provincial bridge in Yogyakarta, which are Srandakan Bridge, Tinalah Brigde, Kebon Agung Brigde, and Glagah Brigde. Data from some other provincial brigdes were also included as a comparison. The evaluations is carried out by imposing 5 series of questions into the object (the damage element of the brigde). Then each element is weighted by point 1 and 0 according to its damage level from the lowest (level 5) until the highest (level 1), which mean the bridge is completely collapse. Its element or groups of element were weighted from 0 to 5 which 5 represent total score of 5 categories. The categories are Structure(S), Level of Damage (R), Damage Volume (K), Element Function (F) and Damage Affect (P). Assessment on the conditions, technical screening and economical evaluations, for Srandakan Bridge, Tinalah Brigde, Kebon Agung Brigde, and Glagah Brigde, resulting the following conditions: 4 (critical – replacement – priority scale 1), 3 (heavily damage – rehabilitation on waterway – priority scale 36), 3 (heavily damage – rehabilitation on upper structure – priority scale 23). Maintenance cost in the economic evaluation aspect is the estimation cost, not the real cost.